3D Printer operation using a design model - T.M. Thamizh Thentral, Ishan Kar, Shubham, A. Geetha, George Fernandez.S (International Journal of Advanced Science and Technology, 2020)
The advancement of the computerized world has brought many laurels to man in the modern era. With this modernization, structures and objects with specified shapes and precisely calculated measurements becomes a major necessity. This necessity puts a huge amount of stress upon traditional handcrafting which in this modern world, has tend to become obsolete. With this transmission, the extensive use of the 3-D printers, which took birth in the late 19th century, possessed a drastic improvement in accuracy and precision and found way towards engineering application. With the scalability of this device to be able to give shape to metals, polymers and powders, it started to be known as a machine able to transmission bulky objects to well-defined patterns and forms. The 3-D printers find their application in vast fields of engineering and technology, including medical, industrial and socio-cultural sectors.The following articles describes in detail, an overview of the 3-D printers, also aiming at developing a 3-D printer, flexible enough to undergo various processes but do not increase the cost of manufacturing. An additive process is defined which includes the reduction of production layers (processes) and materials, stepping the power consumption figure to 50% while a reduction of material usage to 90%.